2018
DOI: 10.1103/physrevlett.120.075301
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Magnetic Boundary Conditions on SuperfluidHe3in Nematic Aerogel

Abstract: We report results of experiments with superfluid 3 He confined in aerogels with parallel strands which lead to anisotropic scattering of 3 He quasiparticles. We vary boundary conditions for the scattering by covering the strands by different numbers of atomic 4 He layers and observe that the superfluid phase diagram and the nature of superfluid phases strongly depend on the coverage. We assume that the main reason of these phenomena is a magnetic channel of the scattering which becomes important at low coverag… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
52
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 43 publications
(54 citation statements)
references
References 50 publications
2
52
0
Order By: Relevance
“…The necessary temperatures were obtained by a nuclear demagnetization cryostat and determined using cw NMR signal from bulk A phase (in gaps between the sample and cell walls) or by a quartz tuning fork calibrated by measurements of the Leggett frequency in bulk 3 He-B. To avoid a paramagnetic signal from surface solid 3 He and stabilize the polar phase [12], the samples were preplated by ∼ 2.5 atomic layers of 4 He.…”
Section: Samples and Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The necessary temperatures were obtained by a nuclear demagnetization cryostat and determined using cw NMR signal from bulk A phase (in gaps between the sample and cell walls) or by a quartz tuning fork calibrated by measurements of the Leggett frequency in bulk 3 He-B. To avoid a paramagnetic signal from surface solid 3 He and stabilize the polar phase [12], the samples were preplated by ∼ 2.5 atomic layers of 4 He.…”
Section: Samples and Methodsmentioning
confidence: 99%
“…(1) belong to a class of Equal Spin Pairing (ESP) states. Previous experiments with 3 He in nematic aerogel were done using samples with strands of AlOOH (Obninsk aerogel) or Al 2 O 3 (nafen) with various porosities and degree of the anisotropy [6,7,8,9,10,11,12]. It was found that on cooling from the normal phase, the superfluid transition of 3 He occurs into the PdA phase (in Obninsk aerogel) or into the polar phase (in nafen).…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, in confined geometry where the PdA phase is observed immediately below T c , no HQVs are found. 44 In our case the PdA phase is obtained via the second-order phase transition from the polar phase with preformed HQVs. We already know 21 that the maximum tension from the spin-soliton in the polar phase (for µ = π/2) is insufficient to overcome HQV pinning.…”
Section: Half-quantum Vortices In the Pda Phasementioning
confidence: 99%
“…In this experiment 4 He is present only to coat the surfaces of nafen to prevent the formation of paramagnetic solid 3 He [24]. The thickness of 4 He on the nafen strands was determined to be approximately 2.5 atomic layers [24]. The surfaces, including the quartz tuning fork, could adsorb more 4 He, thus the 4 He layer was not maximal [24].…”
Section: He With Small Amount Of 4 He Presentmentioning
confidence: 97%
“…A quartz tuning fork in the bulk 3 He volume (QTF2) is used as a thermometer. In this experiment 4 He is present only to coat the surfaces of nafen to prevent the formation of paramagnetic solid 3 He [24]. The thickness of 4 He on the nafen strands was determined to be approximately 2.5 atomic layers [24].…”
Section: He With Small Amount Of 4 He Presentmentioning
confidence: 98%